Pelaksanaan Pengembangan Kapasitas Melalui Kerjasama Pemerintah Provinsi Jawa Timur dan KOICA (Korea International Cooperation Agency) Sebagai Upaya Reformasi Birokrasi (Studi Pada Lingkup Pemerintah Provinsi Jawa Timur) - Rr. Safitri Damayanti (Jurnal Administrasi Publik, 2016)
Abstract: The Implementation of Capacity Building through a Cooperation Between East Java Province and KOICA (Korea International Cooperation Agency) as an Effort of Bureaucracy Reform (Study on the Scope of Government of East Java Province). This study was made aiming to reveal the action of Cooperation between East Java Province and South Korea’s International Non-Government Organization which is KOICA (Korea International Cooperation Agency), in order to building the capacity. This Study is also analyze how important the needs of capacity building in scope of Government of East Java Province, and what kind of strategy which is offered by the participants of capacity building for better Government of East Java Province. This research used descriptive research methods with qualitative approach. Technique of data analysis used for Spradley model analysis. According to the research result, form of cooperation between East Java Province and KOICA is through capacity building which is trained by KOICA in South Korea. The participants are required to give strategy (Action Plan) which chosen one that represent East Java Province’s needs. The strategy which can represent of East Java Province’s needs is Action Plan from Communication and Information Services of East Java Province, and it called E-Commerce. Keywords: capacity building, international non-government organization, bureaucracy reform Abstrak: Pelaksanaan Pengembangan Kapasitas Melalui Kerjasama Pemerintah Provinsi Jawa Timur dan KOICA (Korea International Cooperation Agency) Sebagai Upaya Reformasi Birokrasi (Studi pada Lingkup Pemerintah Provinsi Jawa Timur). Penelitian ini bertujuan untuk mengungkapkan adanya kegiatan kerjasama yang dilakukan Pemerintah Provinsi Jawa Timur dengan lembaga internasional milik Korea Selatan, KOICA (Korea International Cooperation Agency) dalam mengembangkan kapasitas kelembagaan. Penelitian ini menganalisis pentingnya kebutuhan pengembangan kapasitas dalam lingkup Pemerintah Provinsi Jawa Timur, dan strategi yang ditawarkan peserta pengembangan kapasitas dalam membuat Pemerintah Provinsi Jawa Timur menjadi lebih baik. Penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan kualitatif. Teknik analisis data menggunakan model analisis Spradley. Berdasarkan hasil penelitian, bentuk kerjasama antara Pemerintah Provinsi Jawa Timur dan KOICA melalui adanya pengembangan kapasitas yang dilatih oleh KOICA di Korea Selatan. Peserta wajib memberikan strategi (Action Plan) yang kemudian akan dipilih salah satu yang dapat mewakili kebutuhan Provinsi Jawa Timur. Strategi yang dianggap mampu mewakili Kebutuhan Provinsi Jawa Timur adalah Action Plan dari Dinas Komunikasi dan Informatika Jawa Timur, dan disebut dengan E-Commerce. Kata kunci: pengembangan kapasitas, organisasi internasional non pemerintah, reformasi birokrasi